2015
DOI: 10.2147/dddt.s90580
|View full text |Cite
|
Sign up to set email alerts
|

Maraviroc: a review of its use in HIV infection and beyond

Abstract: The human immunodeficiency virus-1 (HIV-1) enters target cells by binding its envelope glycoprotein gp120 to the CD4 receptor and/or coreceptors such as C-C chemokine receptor type 5 (CCR5; R5) and C-X-C chemokine receptor type 4 (CXCR4; X4), and R5-tropic viruses predominate during the early stages of infection. CCR5 antagonists bind to CCR5 to prevent viral entry. Maraviroc (MVC) is the only CCR5 antagonist currently approved by the United States Food and Drug Administration, the European Commission, Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 204 publications
2
41
0
Order By: Relevance
“…15 CCR5 binds CCL2, CCL3, CCL4, CCL5, CCL8, CCL11, CCL13, and CCL14 CC chemokines and is the major HIV-1 coreceptor. 1 The FDA approved CCR5 antagonist 16 (9) is used for the treatment of patients with HIV (R5-tropic HIV-1), and a crystal structure of rubredoxin fused CCR5 bound to 16 (PDB 4MBS, Figures 1d, 3b) has been reported. 12 CCR9 activation by CCL25 plays a key role in leukocyte recruitment to the gut and is a therapeutic target in inflammatory bowel disease.…”
Section: Analysis Of Chemokine Receptor Crystal Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…15 CCR5 binds CCL2, CCL3, CCL4, CCL5, CCL8, CCL11, CCL13, and CCL14 CC chemokines and is the major HIV-1 coreceptor. 1 The FDA approved CCR5 antagonist 16 (9) is used for the treatment of patients with HIV (R5-tropic HIV-1), and a crystal structure of rubredoxin fused CCR5 bound to 16 (PDB 4MBS, Figures 1d, 3b) has been reported. 12 CCR9 activation by CCL25 plays a key role in leukocyte recruitment to the gut and is a therapeutic target in inflammatory bowel disease.…”
Section: Analysis Of Chemokine Receptor Crystal Structuresmentioning
confidence: 99%
“…8 A variety of proteins, peptides, and small-molecule ligands have been identified that can modulate the activity of chemokine receptors 1 by targeting the minor or major pockets in the 7TM helical bundle or intracellular binding pocket (Figures 1–2). Examples of small nonpeptide ligands are the clinically approved drugs 16 (Maraviroc, CCR5 antagonist, Figures 3 and 11) 9 and 1 (plerixafor/AMD3100, CXCR4 antagonist, Figure 11), 10 used for the treatment of HIV and stem cell mobilization, respectively. Molecular pharmacological, medicinal chemistry, and molecular modeling studies have provided insights into molecular determinants of chemokine receptor modulation 1,2,4 and in the past few years the first high-resolution crystal structures of chemokine receptors have been solved that give more detailed structural information on the interaction of chemokine receptors and their ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogen of AIDS is HIV [ 1 ]. HIV entry into CD4+ cells is dependent on the receptor CD4 and co-receptors, such as CCR5 (C-C chemokine receptor 5) or CXCR4 (C-X-C chemokine receptor type 4) on the surface of target cells [ 4 , 6 9 ]. CCR5-tropic viruses predominate most isolates from human bodies globally and usually found in the early HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…CCR5-tropic viruses predominate most isolates from human bodies globally and usually found in the early HIV infection. CXCR4-tropic viruses are fewer, and usually found in the late stage of infection [ 4 , 9 , 10 ]. CCR5 delta 32 mutation is a deletion of 32 base pairs after amino acid position 185, resulting in a premature and non-functional CCR5 receptor [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…One such drug, Maraviroc, is used to treat HIV infection, and also blocks graft versus host disease (a complication of bone marrow transplantation) 9 . The authors find that such agents are more effective at preventing MPN post-transplant than in combatting established JMML in mice.…”
mentioning
confidence: 99%